PREVALENCE OF ENTEROTOXIN TYPE A IN STAPHYLOCOCCUS AUREUS ISOLATED FROM DIFFERENT SOURCES - Kadhim, B. A.; Essa , M. A.; Sabbah, M. R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was aimed to investigate the prevalence of enterotoxin type A in (82) Staphylococcus aureus isolates from different sources(Pathogenic, Soil, Food, Tape water& Nasal swabs from Normal source), the results had shown the capacity of (58) isolates (70.73%) to produce the enterotoxin by using culture method (in solid and liquid medium), concerning the liquid medium, the results conducted that there was a significant differences at P£ 0.05, among bacterial isolates in the amount of produced enterotoxin in terms of optical density. By using serological ELISA specific kit, the results had confirmed the ability of (47) bacterial isolates(57.32%) to produce enterotoxin type A with concentrations were ranged between( 3.7 - 15.7) ng/ml, which represents (81%) of all isolates producing enterotoxins, also the results indicated that there were isolates from different isolation sources can produce this toxin , and the prevalence of enterotoxin type A producing isolates was in pathogenic isolates(43.9%), soil (66.7%), food(92.3%), Tape water(55%) & Nasal swabs(80%), This prevalence of enterotoxin type A which is the most dangerous of Staphylococcal enterotoxins in studied isolates reflects the risk and healthy importance of this bacteria, regardless of the source of its isolation.